Laboratory Rearing of Laricobius nigrinus (Coleoptera: Derodontidae): A Predator of the Hemlock Woolly Adelgid (Hemiptera: Adelgidae) - S. M. Salom; L. T. Kok; A. B. Lamb; C. Jubb (Psyche: A Journal of Entomology)
Coleopteran species are biological control agents of numerous invasive pests. Laricobius nigrinus (Coleoptera: Derodontidae), a predaceous, univoltine species, spends the summer aestivating but is active for the rest of the year. Laricobius nigrinus possesses many essential attributes for effective biological control of the hemlock woolly adelgid (Hemiptera: Adelgidae). The predator must be reared in large numbers for field releases. We describe some of the studies that led to the successful procedures currently used for mass rearing L. nigrinus.